ULK1‐mediated phosphorylation of ATG16L1 promotes xenophagy, but destabilizes the ATG16L1 Crohn's mutant. (24th May 2019) - Alsaadi, Reham M; Losier, Truc T; Tian, Wensheng; Jackson, Anne; Guo, Zhihao; Rubinsztein, David C; Russell, Ryan C
Abstract: Autophagy is a highly regulated catabolic pathway that is potently induced by stressors including starvation and infection. An essential component of the autophagy pathway is an ATG16L1‐containing E3‐like enzyme, which is responsible for lipidating LC3B and driving autophagosome formation. ATG16L1 polymorphisms have been linked to the development of Crohn's disease (CD), and phosphorylation of CD‐associated ATG16L1 T300A (caATG16L1) has been hypothesized to contribute to cleavage and autophagy dysfunction. Here we show that ULK1 kinase directly phosphorylates ATG16L1 in response to infection and starvation. Phosphorylated ATG16L1 localizes to the site of internalized bacteria and stable cell lines harbouring a phospho‐dead mutant of ATG16L1 have impaired xenophagy, indicating a role for ATG16L1 phosphorylation in the promotion of anti‐bacterial autophagy. In contrast to wild‐type ATG16L1, ULK1‐mediated phosphorylation of caATG16L1 drives its destabilization in response to stress. In summary, our results show that ATG16L1 is a novel target of ULK1 kinase and that ULK1 signalling to ATG16L1 is a double‐edged sword, enhancing the function of the wild‐type ATG16L1, but promoting degradation of caATG16L1. Synopsis: ULK1 phosphorylates ATG16L1 on S278 to promote autophagic activity of wild‐type ATG16L1. In contrast, this regulation enhances caspase‐mediated degradation of Crohn‐associated (T300A) ATG16L1, thereby reducing xenophagy and bacterial clearance. ULK1 phosphorylates ATG16L1 on S278. Starvation and bacterial infection induce ULK1‐mediated ATG16L1 regulation. ULK1 signalling to ATG16L1 enhances the function of wild‐type ATG16L1 while degrading Crohn‐associated (T300A) ATG16L1. Abstract : ULK1 phosphorylates ATG16L1 on S278 to promote autophagic activity of wild‐type ATG16L1. In contrast, this regulation enhances caspase‐mediated degradation of Crohn‐associated (T300A) ATG16L1, thereby reducing xenophagy and bacterial clearance.